Buckling analysis of CNTRC plates in the thermal environment based on combination of the incremental load technique and dynamic relaxation method. Issue 4 (4th July 2021) - Golmakani, M. E.; Esmaeilzadeh, M.; Sadeghian, M.; Zeighami, V.
Abstract: In this article, the buckling of composite plates reinforced with functionally graded distributions of single-walled carbon nanotubes along the thickness direction are studied in the thermal surroundings. The properties of carbon-nanotubes reinforced composite (CNTRC) plate were determined through the modified rule of mixture. All governing equations are obtained incrementally based on first-order shear deformation theory and von Karman nonlinear strain. The nonlinear equilibrium equations are solved through a combination of dynamic relaxation and incremental load methods. A detailed parametric study is carried out to investigate the buckling load of nanocomposite plates with different boundary conditions.